2023
DOI: 10.1371/journal.pcbi.1010938
|View full text |Cite
|
Sign up to set email alerts
|

Coding of object location by heterogeneous neural populations with spatially dependent correlations in weakly electric fish

Abstract: Understanding how neural populations encode sensory stimuli remains a central problem in neuroscience. Here we performed multi-unit recordings from sensory neural populations in the electrosensory system of the weakly electric fish Apteronotus leptorhynchus in response to stimuli located at different positions along the rostro-caudal axis. Our results reveal that the spatial dependence of correlated activity along receptive fields can help mitigate the deleterious effects that these correlations would otherwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…For the experiments in Figs. 8 F and 9 simultaneous extracellular recordings from ELL pyramidal cells were made using Neuropixels probes (Imec Inc.) as done previously 113 116 . The probe was angled at approximately 15 deg.…”
Section: Methodsmentioning
confidence: 99%
“…For the experiments in Figs. 8 F and 9 simultaneous extracellular recordings from ELL pyramidal cells were made using Neuropixels probes (Imec Inc.) as done previously 113 116 . The probe was angled at approximately 15 deg.…”
Section: Methodsmentioning
confidence: 99%
“…The average baseline firing rate was 20.5 ± 11.1 spks/s (4.1–64.7 spks/s), which is similar to that reported in previous studies. 56 , 104 , 106 , 107 We note that other cell types within the ELL (e.g., interneurons) typically display firing rates higher than those of ELL pyramidal cells. 108 …”
Section: Methodsmentioning
confidence: 79%
“…We classified each cell as being either ON-type or OFF-type based on the spike triggered-average (STA) to the 5-15 Hz carrier waveform as done previously. 107 , 111 , 112 Specifically, ON- and OFF-type cells fire action potentials during carrier up- and downstrokes, respectively (see Figure S1 ). As such, the slope of the STA preceding the action potential will be positive for ON-type cells and negative for OFF-type cells.…”
Section: Methodsmentioning
confidence: 99%
“…The heterogeneity of neuron properties has received much interest lately: for instance, it has been shown that heterogeneity in neural populations can increase coding robustness and efficiency [ 48 ], help optimize information transmission [ 80 ], increase network responsiveness [ 81 ], promote robust learning [ 82 ], help to control the dynamic repertoire of neural populations [ 83 ] and improve the performance on several tasks [ 84 , 85 ]. Here, we show that in particular, the population of excitatory neurons of the barrel cortex shows a large variability in their intrinsic and response properties.…”
Section: Conclusion and Discussionmentioning
confidence: 99%